Linear perturbation constraints on multi-coupled dark energy - Piloyan, Arpine; Marra, Valerio; Amendola, Luca (Arxiv, 2014)
The Multi-coupled Dark Energy (McDE) scenario has been recently proposed as a specific example of a cosmological model characterized by a non-standard physics of the dark sector of the universe that nevertheless gives an expansion history which does not significantly differ from the one of the standard $Λ $CDM model. In this work, we present the first constraints on the McDE scenario obtained by comparing the predicted evolution of linear density perturbations with a large compilation of recent data sets for the growth rate